2016
DOI: 10.1177/0734282916639462
|View full text |Cite
|
Sign up to set email alerts
|

Test-Taking Speed: Predictors and Implications

Abstract: Students often feel time pressure when taking tests, and students with disabilities are sometimes given extended time testing accommodations, but little research has been done on the factors that affect students’ test-taking speed. In the present study, 253 students at two colleges completed measures of processing speed, reading fluency, and self-reports of their reading and test-taking skills, as well as a standardized paper-and-pencil reading comprehension task. The time taken to complete the reading compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…While we did not find group differences on reading performance measures, we did find participants with disabilities reported significantly more concerns about their reading and test-taking abilities than peers. Similar findings have been reported in other studies (Lewandowski, Berger, Lovett, & Gordon, 2016; Lovett, Lewandowski, & Potts, 2017), suggesting that college students tend to perceive more reading or learning problems than they demonstrate on standardized tests. Despite this apparent disconnect, we found that perception of reading and test taking did significantly predict amount of time used on the comprehension test.…”
Section: Discussionsupporting
confidence: 90%
“…While we did not find group differences on reading performance measures, we did find participants with disabilities reported significantly more concerns about their reading and test-taking abilities than peers. Similar findings have been reported in other studies (Lewandowski, Berger, Lovett, & Gordon, 2016; Lovett, Lewandowski, & Potts, 2017), suggesting that college students tend to perceive more reading or learning problems than they demonstrate on standardized tests. Despite this apparent disconnect, we found that perception of reading and test taking did significantly predict amount of time used on the comprehension test.…”
Section: Discussionsupporting
confidence: 90%
“…Other findings are relatively less surprising and align well with the literature. In particular, there is evidence that speed on a reading comprehension test is not related to reading comprehension performance (Lovett et al, 2017) which reflects the results that VRRC items are weakly discriminating on test-speed.…”
Section: Discussionmentioning
confidence: 94%
“…Into the twenty-first century, the prediction continues to fail not only in psychology courses (Brothen, 2012;Hammonds & Mariano, 2015) but also in chemistry (Ghaffari, 2015;Nevo & Spector, 1979); engineering (Armitage, 1999); agriculture (McDannell & Lyvers Peffer, 2013); business, including finance, real estate, and management (Beaulieu, & Frost, 1994;Lee, 2012;Schnusenberg & Slater, 2011); English and literature (Lovett, Lewandowski, & Potts, 2017;Rogers, 1968); statistics (Hammonds & Mariano, 2015;Onwuegbuzie & Daley, 1996); and mathematics (Rogers, 1968). Why does the prediction fail?…”
Section: Time-limited Tests Are Less Validmentioning
confidence: 99%